Development and evaluation of an application-based system with LINE chatbot for pesticide-exposure risk assessment among sugarcane farmers - Peanthip Srisutam; Rattana Leerungnavarat; Chan Pattama Polyong (Journal of Public Health and Development, 2026)
This study developed and evaluated a mobile application integrated with a LINE chatbot for assessing pesticide-use behaviors and related health risks among rice and sugarcane farmers in Thailand. A research and development (R&D) design combined with a quasi-experimental approach was applied, using the standardized assessment tool of the Department of Disease Control. Expert evaluation (n=3) confirmed strong content validity (IOC =0.67–1.00) and reliability testing with30participants(n=30), including health officers and volunteers (Cronbach’s alpha 0.729), Indicated very high satisfaction, particularly regarding convenience, clarity of results, and applicability. Field testing with 125 farmers (n=125) showed that unsafe practices were highly prevalent, including self-spraying herbicides (85.6%), not reading labels (82.4%), and not washing hands before meals (81.6%). Symptom monitoring revealed that 74.6% of farmers reported health problems, mainly at moderate severity (55.1%), with dizziness, nausea, and abdominal pain being common. Overall risk assessment classified 38.9% of farmers as high risk, 27.1% as moderately high risk, and only 7.9% as low risk. The application significantly reduced assessment and reporting time compared with paper-based methods (mean total time: 22.6 vs. 3.2 minutes, p